2007
DOI: 10.1111/j.1542-474x.2007.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Atrial Substrate Change after Wide Area Circumferential Ablation: A Comparison with Segmental Pulmonary Vein Isolation

Abstract: HR recordings exhibit change in HRV after WACA and PVI. Marked change in both HRV and SAPW is observed after WACA. SAPW variables provide a measure of atrial substrate change after WACA unrelated to autonomic denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The results of these studies are conflicting. Some studies showed that is the technique was useful to predict recurrences [25], 26], [27] whereas other data did not [28], probably because of different study design, small numbers of patients, various SAECG methodologies and variable definition of recurrences. The high recurrence rate in our study was essentially due to use of the nMARQ catheter with low power settings, which was probably a confounding factor with reconnection of the pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies are conflicting. Some studies showed that is the technique was useful to predict recurrences [25], 26], [27] whereas other data did not [28], probably because of different study design, small numbers of patients, various SAECG methodologies and variable definition of recurrences. The high recurrence rate in our study was essentially due to use of the nMARQ catheter with low power settings, which was probably a confounding factor with reconnection of the pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies [25], 26], [27], [28] have used the SAECG to study the effect of RF catheter ablation on the P-wave and to predict the risk of recurrences after ablation. The results of these studies are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, re‐conduction is not the only possible cause (Callans et al, ; Gerstenfeld, Callans, Dixit, Zado, & Marchlinski, ). These causes include extra PV foci, atrial substrate remodeling leading to conduction delays (Van Beeumen, Houben, Tavernier, Ketels, & Duytschaever, ; Callans et al, ; Gerstenfeld et al, ; Ogawa et al, ; Redfearn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous mechanistic study had shown that PVI performed by the WACA technique was likely to cause greater atrial remodeling, as demonstrated by surrogate electrophysiological parameters (signal averaged P-wave duration), compared to a segmental approach. The better success rates associated with the WACA technique was attributed to a greater degree of modification of the atrial substrate (positive remodeling) compared to the segmental PVI technique [9]. The fact that all subjects in the current study underwent PVI using the WACA technique should have resulted in nearly similar extent of atrial substrate modification after catheter ablation and should not have influenced the incidence of AF recurrence.…”
Section: Electrophysiological Parameters As Surrogates For Atrial Remmentioning
confidence: 75%